CHARACTERISTICS AND CLINICAL MANIFESTATIONS OFE-CIGARETTE OR VAPING USE–ASSOCIATED LUNG INJURY (EVALI) - A.Muh. Nasywan Akbar; Edward Pandu Wiriansyah; Bulkis Natsir (The Indonesian Journal of General Medicine, 2026)
Electronic cigarettes (e-cigarettes) have been the most commonly used tobacco products among young people since 2014. E-cigarettes are battery-operated devices that heat a liquid to produce an aerosol containing various active chemical substances. This study aimed to describe the characteristics and clinical manifestations of E-cigarette, or Vaping, Product Use–Associated Lung Injury (EVALI). The study was conducted by collecting secondary data from multiple research journals published between 2020 and 2025. The results indicate that EVALI is a lung disease associated with the use of e-cigarettes or vaping products. The clinical manifestations of EVALI are heterogeneous but commonly include respiratory symptoms, constitutional symptoms (such as fever and fatigue), and gastrointestinal symptoms. EVALI is caused by exposure to chemical substances contained in vaping products, including tetrahydrocannabinol (THC), nicotine, and other additives. During the epidemic period, EVALI management has not yet had standardized guidelines regarding dosing and treatment stratification. The management of EVALI is divided into non-pharmacological and pharmacological approaches. The complexity of diagnostic procedures required for EVALI results in most diagnosed patients being hospitalized, with oxygen saturation levels below 95% at the time of hospital admission.